2014
DOI: 10.1167/iovs.13-13075
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effect of Sodium Iodate on Neurosensory Retina

Abstract: Systematic characterization of changes associated with NaIO3 injection revealed a large variability in the severity of toxicity induced. Treatment with >20 mg/kg NaIO3 induced visual dysfunction associated with rapid suppression of phototransduction genes and induced oxidative stress in photoreceptors. These results suggest that NaIO3 can directly alter photoreceptor function and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 37 publications
12
128
0
Order By: Relevance
“…[15][16][17] In these studies, the toxin was administered systemically resulting in patchy panretinal degeneration. To better mimic clinical GA we sought to explore subretinal administration of NaIO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] In these studies, the toxin was administered systemically resulting in patchy panretinal degeneration. To better mimic clinical GA we sought to explore subretinal administration of NaIO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…These results essentially confirmed previous observations using systemically administered NaIO 3 , for which the morphologic and molecular effects have been characterized extensively in rabbit and rodent models. [15][16][17] Early ultrastructural studies in rabbit demonstrated the first retinal changes to occur in the RPE already after 7 to 10 hours with subsequent photoreceptor swelling and degeneration. 15 Later studies have shown that lower doses of NaIO 3 cause patchy RPE loss whereas higher doses lead to widespread RPE loss within 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…13 Whether or not primary damage occurs in additional retinal structures is still a matter of debate. [14][15][16] However, because it allows controlled onset and progression (for instance, induction in an adult animal), this model may provide benefit for studying novel modalities for treatment of retinal degeneration caused by RPE dysfunction beyond the genetic models that are often used for this purpose.…”
mentioning
confidence: 99%
“…25 Our hypothesis stated that the increased miR-183 cluster in the circulating blood was due to the leakage of RPE and Bruch's membrane by NaIO 3 toxicity. There is a possibility that cells of the neurosensory retina (ganglion cell, amacrine, or horizontal cells) 45 and photoreceptors 46 may also be directly involved in NaIO 3 -mediated toxicity. To date, this is the first report describing the plasma miRNA profile in a nonhuman primate in response to toxic doses of intravenously administered NaIO 3 , therefore the translatability of the nonhuman primate data to the human as well as the neuronal/ neurotrophic factor pathways associated with the neuronal retina injury remains to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%